Difficulties and Possible Escapes from Central Europe’s Demographic Winter: A Summary of Best Practices - Barzó, Tímea (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
The final chapter of the volume is a synthesis study, which aims to summarise the main regulatory features of the country reports in a logical order. However, the study does not focus solely on the specificities of Central Europe, but also takes a more holistic approach, drawing on the first part of the volume, and briefly reviews the demographic situation in the world and in Europe, as well as the related regulatory environment of the European Union.Keywords: family policy, ageing society, population of Central Europe, fertility rate, demographic challenge of Central Europe, best practices of demographic winter